Laboratory medicine management: Leadership skills for effective laboratory - Majkić-Singh Nada (Journal of Medical Biochemistry, 2017)
Forum of the European Societies of Clinical Chemistry (FESCC) decided that the FESCC Symposium for Balkan Region would be held each year in Belgrade and organized by the Society of Medical Biochemists of Serbia and Montenegro (SMBSM). Professor Victor Blaton, at the time President of the FESCC, supported the organization of the Symposium. Purpose of these Symposia has been to educate clinical biochemists from Balkan region to improve management, leadership skills for effective laboratories. As a result of these decision twelve symposia have been organized thus far very successfully. Here the most important Symposium topics will be reviewed. Also, the 13th EFLM Symposium for Balkan Region under the title "Laboratory Medicine Management: Leadership Skills for Effective Laboratory" (Belgrade, September 2017) is organized by EFLM and SMBS under the Auspices of the International Federation of Clinical Chemistry (IFCC), Ministry of Education, Science and Technological Development of Serbia and Ministry of Health of Serbia with participation of the European and domestic specialists in field of Laboratory Medicine.